Policy Analysis for Building Resilience in the Maritime Area Through Bhakti Operations in Coastal Communities - Hariono Hariono; Arif Darmawan; Agus Sukristyanto (Syntax Corporation Indonesia, 2024)
Coastal areas have large potential economic resources and are full of problems that disturb and threaten the country's defense and security. So it is important to empower coastal communities as objects of non-military operations using various approaches. For this reason, this research aims to analyze policies for developing maritime area resilience (Bintahwilmar) through community service operations in coastal communities. This qualitative research with a descriptive analysis approach takes policy objects in the Pangkalan Utama V Surabaya area, and collects data through documents and interviews. Analysis was carried out using a data interpretation approach. The results of the policy analysis can explain that coastal area development requires a holistic and collaborative approach involving the government, Indonesian Navy, local communities and various related parties. Community welfare is an important aspect in developing coastal areas, including through renovation programs and building livable houses. Cooperation between the government and the Indonesian Navy is based on the principles of democracy, human rights, transparency, accountability, community participation and environmental sustainability between the East Java Provincial Government and the Indonesian Navy. An important finding from this research is that the principles and elements underlying Ansell Collaborative Governance demonstrate the relevance and applicability of policy analysis models in the context of coastal development.